Spatial and temporal variations in methane fluxes from irrigated lowland rice fields - Gaihre, Y. K.; Tirol-Padre, A.; Wassmann, R.; Aquino, E.; Pangga, G. V.; Sta. Cruz, P. C. (2011)
An assessment of spatial and temporal variations in methane (CH4) emission was conducted in three experimental fields (UQ, UY and UE) of the International Rice Research Institute Experimental Farm in Bay, Laguna, Philippines during the 2009 dry season. Aside from CH4 fluxes, the following parameters were also determined: hot water-extractable C (HWEC), floodwater temperature (FWT), floodwater depth (FWD) and plant height. Field sampling was conducted using static chambers and CH4 concentrations were analyzed using a gas chromatograph. The highest average emission rate was observed in field UQ, followed by UE and UY (651, 107 and 95 mg CH4 m-2 d-1, respectively). The UQ field also had the highest average HWEC (618 mg kg-1 compared with 496 for UY 496 and 482 for UE). Significant temporal variations in CH4 emission, HWEC and FWT were observed within each field. Stepwise multiple regression analysis showed that HWEC, plant height, FWT and FWD accounted for 62% of the spatial and temporal variabilities in CH4 fluxes. Soil HWEC showed the greatest contribution (R2 = 0.46, P < 0.0001), followed by plant height (R2 = 0.11, P < 0.0001), FWT (R2=0.03, P < 0.04) and FWD (partial R2=0.02, P < 0.07). Key Words: flooded rice, hot water-extractable carbon, methane emission
Keywords: Methane; Rice field irrigation